Action plan for metrication in Antigua and Barbuda (The Secretariat LondonGB, 2005)
Provides a framework for undertaking a systematic change to the metric system. Sets out the policy guidelines and strategies that are necessary to operationalize the changeover within the next three or four years. Details the approach to be followed in the various sectors of the economy. Specifies in broad terms how the sector priorities should be pursued in order to complete the metrication changeover in a successful manner.
Keywords: METRIC SYSTEM